2019
DOI: 10.21203/rs.2.16016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gun Violence Restraining Order Laws and Firearm Suicide among Older Adults: A Longitudinal State-Level Analysis

Abstract: Background: Older adults commit suicide at a disproportionately higher rate compared to the general population, with firearms the most common means of suicide. State gun laws may be a policy remedy. Less is known about Gun Violence Restricting Order (GVRO) laws, which allow for removal of firearms from people deemed to be a danger to themselves or others, and their effects on suicide rates among older adults. The purpose of this study was to examine the association of state firearm laws with the incidence of f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…9,10 Decreasing availability of firearms in depressed older adults has been demonstrated to decrease suicide incidence in this population. 11…”
Section: Background On Firearm Suicidementioning
confidence: 99%
“…9,10 Decreasing availability of firearms in depressed older adults has been demonstrated to decrease suicide incidence in this population. 11…”
Section: Background On Firearm Suicidementioning
confidence: 99%
“…The study showed that the total number of firearm laws was negatively associated with firearm-related suicide and the total number of suicides among both age groups. Similarly, ERPOs were associated with a reduction in firearm suicides (> 2 % for both age groups) and a reduction in total suicide deaths in both age groups [58].…”
Section: Population-based Interventionsmentioning
confidence: 82%
“…The promise of state firearm laws as it relates to firearm suicides in the elderly is marred by several limitations [56][57][58][59][60][61]. First, most studies on firearm laws and suicides do not exclusively focus on the elderly population, a major limitation given the unique socioeconomic and lifestyle circumstances of the elderly.…”
Section: Population-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 A recent longitudinal study showed that GVROs could be effective in decreasing suicides in elderly males; the same population that we found to be highest risk in our study. 38 More prospective studies that can comprehensively compare gun legislation, suicide screening programs, and GVROs as interventions in different regions, counties, states in the U.S should be performed to investigate the effectiveness of these strategies in the prevention of firearm suicides.…”
Section: Discussionmentioning
confidence: 99%